Unraveling the complexity of nurses’ quality of life: A Fuzzy-Set Qualitative Comparative Analysis (fsQCA) approach to the interplay of psychological, occupational, and social factors - Xu Jun; Li Shasha; Mao Dandan (PLoS ONE, 2026)
Aim This study aimed to explore the interplay among occupational stress, psychological distress, social support, burnout, and work-family conflict in relation to the quality of life (QOL) of nurses. Methods A total of 503 nurses from two tertiary-level hospitals participated in an online survey. Data were collected on psychological distress, occupational stress, social support, burnout, work-family conflict, and quality of life. Fuzzy-set Qualitative Comparative Analysis (fsQCA) was conducted to identify configuration pathways associated with high and low QOL, thereby providing a nuanced understanding of the causal complexity underlying these outcomes. Results Four configuration pathways were identified as conducive to high QOL: (H1) low burnout, low occupational stress, and high social support; (H2) low work-family conflict, low burnout, low occupational stress, and low psychological distress; (H3) high social support, low work-family conflict, low occupational stress, and low psychological distress; and (H4) high social support, low work-family conflict, low burnout, and low psychological distress. Conversely, two pathways were associated with low QOL: (L1) high occupational stress, high psychological distress, high work-family conflict, and low social support; and (L2) high occupational stress, high psychological distress, high work-family conflict, and high burnout. Conclusion Nurses’ QOL is critically influenced by occupational and psychological stressors, work-family conflict, and social support. Addressing these factors through targeted interventions may reduce burnout and psychological distress while enhancing well-being and job satisfaction.